Cultural Representation in Global Film Discourse: A Bibliometric Analysis of Dominant Themes and Western Hegemony - Hijriyani, Nur Fajri; Arienda, Hanun Dzikra; Firmansyah, Firmansyah; Hariadi, Nur Wijaya; Sonni, Alem Febri (UI Scholars Hub, 2025)
This study investigates the dominant themes and discursive structures within global film scholarship through a bibliometric analysis of 404 Scopus-indexed articles published between 2019 and 2024. Using VOSviewer to map keyword co-occurrence, citation networks, and authorship patterns, the research identifies five major thematic clusters: Hollywood, feminism, representation, Bollywood, and popular culture. The findings reveal a persistent dominance of Western narratives positioning them at the centre of global film studies. In contrast, themes related to non-Western cinema, such as Bollywood, appear less central and more fragmented within the academic discourse. These results highlight how bibliometric patterns reflect broader ideological structures, reinforcing Stuart Hall’s theory of cultural representation and the asymmetry of global meaning production. The study concludes that while Western hegemony remains influential, there is emerging scholarly attention to diverse cultural narratives. Future research should incorporate more inclusive data sources and methodologies to better capture underrepresented voices in global film discourse.